Are ‘new’ donors different?: comparing the allocation of bilateral aid between nonDAC and DAC donor countries - Dreher, Axel; Nunnenkamp, Peter; Thiele, Rainer (World development, 2011)
Major DAC donors are widely criticized for weak targeting of aid, selfish aid motives, and insufficient coordination. The emergence of an increasing number of new donors may further complicate the coordination of international aid efforts. At the same time, it is open to question whether new donors (many of which were aid recipients until recently) are more altruistic and provide better targeted aid according to need and merit. Project-level data on aid by new donors, as collected by the AidData initiative, allow for empirical analyses comparing the allocation behavior of new versus old donors. We employ Probit and Tobit models and test for significant differences in the distribution of aid by new and old donors across recipient countries. We find that, on average, new donors care less for recipient need than old donors. New and old donors behave similarly in several respects, however. They disregard merit by not taking the level of corruption in recipient countries into account. Concerns that commercial self-interest distorts the allocation of aid seem to be overblown for both groups.